Rickettsia with Atypical Presentation in Rural Population - Gurumurthy, Vaishnavi; Jain, Gauri (Archives of Clinical and Medical Case Reports, 2023)
Rickettsia species are small, Gram-negative bacilli that are obligate intracellular parasites of eukaryotic cells. Incidence of Rickettsia have been found in various states of India. Over the last decade, there has been rising incidence of Rickettsia infection in the rural population of Indian subcontinent. The pathogenesis of Rickettsia is varied because of which there are high chances of atypical presentation to the hospital. One such atypical symptom is edema. Due to inflammation of endothelial cells of the blood vessel, extravasation of fluid occurs causing edema and acute kidney injury.